HUMAN RESOURCE DEVELOPMENT AND ORGANIZATIONAL PERFORMANCE IN LOCAL GOVERNMENT COUNCILS, RIVERS STATE, NIGERIA (American Journal of Business Management, Economics and Banking, 2024)
This study examined human resource development and organizational performance in local government councils, Rivers State, Nigeria. The researcher concentrated on training and mentoring as measures of human resource development whereas customer satisfaction and employee satisfaction were carefully regarded as proxies of organizational performance. Population size for the study was 341 employees selected from 12 local government councils, Rivers State. The sample size was 184 employees including head of personnel management (HPM), director of budget, and senior staff chosen from local government councils. Taro Yamane’s formula was used to determine the sample size. The researcher adopted a cross-sectional descriptive research design random sampling method. Instrument used for data collection were primarily questionnaire and information from Rivers State local government service commission bulletin. The hypotheses were tested using spearman correlation coefficient. The findings indicated that there was significant positive relationship between training and customer satisfaction in the local government councils. The researcher concluded that an increase in human resource development leads to high performance in local government councils. The researcher also recommends that chairmen of local government councils should provide opportunities for training of both employees and political appointees to create customer satisfaction and high performance or dividend of democracy.